A DEMETER-like DNA demethylase governs tomato fruit ripening - Liu, Ruie; How-Kit, Alexandre; Stammitti, Linda; Teyssier, Emeline; Rolin, Dominique; Mortain-Bertrand, Anne; Halle, Stefanie; Liu, Mingchun; Kong, Junhua; Wu, Chaoqun; Degraeve-Guibault, Charlotte; Chapman, Natalie H.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
In plants, genomic DNA methylation which contributes to development and stress responses can be actively removed by DEMETER-like DNA demethylases (DMLs). Indeed, inArabidopsisDMLs are important for maternal imprinting and endosperm demethylation, but only a few studies demonstrate the developmental roles of active DNA demethylation conclusively in this plant. Here, we show a direct cause and effect relationship between active DNA demethylation mainly mediated by the tomato DML, SlDML2, and fruit ripening—an important developmental process unique to plants. RNAiSlDML2knockdown results in ripening inhibition via hypermethylation and repression of the expression of genes encoding ripening transcription factors and rate-limiting enzymes of key biochemical processes such as carotenoid synthesis. Our data demonstrate that active DNA demethylation is central to the control of ripening in tomato.